Laparoscopic surgery in gynecologic oncology and experience at the Instituto Nacional de Enfermedades Neoplasicas, Lima, Peru - Valdivia, Henry (2015)
Laparoscopic surgery has had an incursion in gynecologic oncology since the 80s. Its applicability is yet controversial, but last few years evidence allows strong consideration of the technique without forgetting possible adverse effects and consequences of an inadequate management. Methods: We reviewed literature data on indications, long time results, comparative studies and advances. We present our own experience. Results: The literature points out the feasibility and advantages of laparoscopy over laparotomy with regards to intraoperatory bleeding, postoperative pain, post surgical hospitalization days and reincorporation to daily activities. Survival results are similar. Extraperitoneal aortic lymphadenectomy is a new useful tool in the management of gynecologic tumors. Laparoscopy is amply used in uterine, endometrial and ovarian cancer treatment. New techniques are being developed such as pelvic exenteration or intraperitoneal hyperthermia chemotherapy by laparoscopy. Conclusions: The literature shows world increasing interest on this technique that should be part of the gynecologic oncologist abilities. Morbidity and recurrence risk should not be affected. Cost-efficacy value may be represented by the decrease in postoperative hospitalization even that surgical time increases initially. It is also important to consider adequate trianing in order to avoid suboptimal management of gynecologic tumors.